2021
DOI: 10.3390/ijms22094423
|View full text |Cite
|
Sign up to set email alerts
|

A Sex Perspective in Neurodegenerative Diseases: microRNAs as Possible Peripheral Biomarkers

Abstract: Sex is a significant variable in the prevalence and incidence of neurological disorders. Sex differences exist in neurodegenerative disorders (NDs), where sex dimorphisms play important roles in the development and progression of Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. In the last few years, some sex specific biomarkers for the identification of NDs have been described and recent studies have suggested that microRNA (miRNA) could be included among these, as influenced by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 100 publications
1
22
0
Order By: Relevance
“…These results suggest higher male susceptibility toward Q78 pathology. This result is in line with available literature in humans, which report gender bias in the progression of many neurodegenerative conditions (Hanamsagar and Bilbo, 2016;Piscopo et al, 2021). We also observed wing defects in eclosed flies on the expression of Q78 protein.…”
Section: Expression Of Mutant Q78 In Motor Neurons Leads To Various B...supporting
confidence: 93%
“…These results suggest higher male susceptibility toward Q78 pathology. This result is in line with available literature in humans, which report gender bias in the progression of many neurodegenerative conditions (Hanamsagar and Bilbo, 2016;Piscopo et al, 2021). We also observed wing defects in eclosed flies on the expression of Q78 protein.…”
Section: Expression Of Mutant Q78 In Motor Neurons Leads To Various B...supporting
confidence: 93%
“…Although we analyzed repeated measures of cognitive function, this study is limited to a single plasma miRNA measure, and thus it is unknown how the abundance of these circulating miRNAs may fluctuate over time. Lastly, these results are based on a cohort of older, mostly white men and may be generalizable only to populations with similar characteristics [ 50 ]. However, the results of our KEGG enrichment analyses are in close agreement with another study that examined the plasma EV-miRNA profile of patients with AD that were mostly female (4 out of 5) and healthy controls that were younger and contained an equal balance of males and females [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current study shows that the occurrence of PD is different in gender, and it is also correlated with the onset age to a certain extent. Previous studies have shown that miRNAs, which can be used as plasma markers, are also gender-dependent in the expression of PD ( Piscopo et al, 2021 ). The biological significance of this sex association has not been clarified, but an increase in the prevalence of PD in men has been recognized.…”
Section: Discussionmentioning
confidence: 99%